HER2 expression and relevant clinicopathological features in gastric and gastroesophageal junction adenocarcinoma in a Chinese population - Shan, Ling (BioMed Central, 2013)
BACKGROUND: With varied immunohistochemistry scoring criteria and patient cohorts, HER2-positivity rates in gastric cancer (GC) and gastroesophageal junction (GEJ) adenocarcinoma have been reported with a wide range. Recently standardized scoring criteria for GC and GEJ cancer has been established and recommended. In this study, the frequency of HER2 expression and the relationship between HER2 expression and clinicopathological features were examined in a large cohort of Chinese GC and GEJ cancer patients. METHODS: A total of 1463 patients, including 929 primary GCs and 534 primary GEJ adenocarcinomas, was retrospectively analyzed for HER2 overexpression by immunohistochemistry (IHC). Fluorescence in situ hybridization (FISH) analysis was used in 308 GCs and GEJ adenocarcinoma cases to assess HER2 gene amplification. RESULTS: HER2 overexpression (3+) was detected in 9.8% of carcinomas and more frequently observed in GEJ cancer cases, in the intestinal type, and in the well or moderately differentiated type (P=0.003, 0.000, and 0.000, respectively). HER2 equivocal (2+) was detected in 14.4% of cases. As for the 308 cases analyzed by FISH, 39 (of 40, 97.5%) IHC 3+ cases, 11 (of 38, 28.9%) IHC 2+ cases, and 3 (of 230, 1.3%) IHC 1+/0 cases showed HER2 gene amplification. A high concordance rate (98.5%) between IHC and FISH was demonstrated. CONCLUSIONS: Approximately 10% of Chinese patients with primary GC and GEJ adenocarcinoma were HER2-positive on IHC. HER2 overexpression was associated with GEJ site, intestinal cancer subtype, and well or moderately differentiated carcinomas. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1935951199941072.